Viral Hepatitis Endemicity and Trends among an Asymptomatic Adult Population in Ho: A 5-Year Retrospective Study at the Ho Municipal Hospital, Ghana. (6th November 2017) - Lokpo, Sylvester Yao; Osei-Yeboah, James; Norgbe, Gameli Kwame; Owiafe, Patrick Kwasi; Ayroe, Felix; Ussher, Francis Abeku; Dakorah, Mavis Popuelle; Gameli Deku, John; Manaphraim, Nana Yaw Barimah; Akomanin Asiamah, Emmanuel; Ntoni, Tibemponi; Senyo Kwasi Nyamadi, Prince; et al.
Abstract : Background . Using prospective blood donors as a proxy, this study was aimed at estimating the burden and five-year (2012–2016) trend of viral hepatitis (HBV and HCV) infection among asymptomatic adult population in Ho. Materials and Methods . A retrospective analysis was done on secondary data extracted from the hospital archives comprising 4, 180 prospective blood donors from January 2012 to December 2016. Demographic variables included age and sex, as well as place of residence. Screening results of serum infectious markers (HBV and HCV) were obtained. Results . The prevalence of asymptomatic viral hepatitis (HBV and HCV) infection in the general adult population was 6.94% and 1.84%, respectively. Females recorded a higher burden of HBV and HCV (8.3% and 5.0%) compared to their male peers (6.8% and 1.4%). A significant age variation in HBV antigenaemia was seen with HBV seropositivity peaking among the younger population (less than 20 years' group) at 11.24% and troughed among the older population (above 50 years' group) at 0.92%. Conclusion . Asymptomatic viral hepatitis among adult population in the Ho Municipality is estimated at the intermediate to high endemicity level. Preventive measures to reduce the burden are urgently needed and should be targeted at the younger generation.